Root Surface Bio-modification with Erbium Lasers- A Myth or a Reality?? - Lavu, Vamsi (Open Dent J, 2015)
The objective of this literature review was to critically review the evidence available in the literature regarding the expediency of erbium family of lasers for root bio modification as a part of periodontal therapy. The literature search was performed on the Pubmed using MeSH words such as "lasers/therapeutic use, scaling, dental calculus, tooth root/anatomy and histology, ultrasonic therapy". The studies were screened and were grouped as follows: those evaluating a) efficacy for calculus removal with the Erbium family of laser b) root surface changes following Er YAG and Er Cr YSGG application c) comparative studies of the Er YAG, Er Cr YSGG lasers versus conventional methods of root surface modification d) Bio compatibility of root surface following Erbium laser treatment e) Studies on the combined efficacy of laser root modification with conventional methods towards root surface bio-modification f) Studies on effectiveness of root surface bio-modification prior to root coverage procedures. In conclusion, the erbium family has a proven anti-bacterial action, predictable calculus removal, minimal root substance removal, and appears to favor cell attachment. The Erbium family of lasers appears to be a useful adjunct for the management of periodontal disease.